Identification of cardiac premature senescence markers through GEO database interaction approach - Tiwuk Susantiningsih; Ani Retno Prijanti; Novi Silvia Hardiany; Fadilah (Indonesian Society for Biochemistry and Molecular Biology, 2024)
Background: Cardiomyocytes are cardiac muscle cells where premature senescence can occur. The availability of in silico research regarding premature senescence in cardiomyocytes is still limited. Purpose: This in silico research aims to identify marker of cardiac premature senescence through the GEO database interaction approach. Methods: This research used the GEO database with the GeneCards website approach using four keywords: premature senescence AND cardiovascular AND cardiomyocytes AND p53 followed by Cytoscape 3.9.1 analysis and StringDB analysis. Results: From 1,046 proteins obtained, analyzed by using Cytoscape Tools series 3.9.1 resulted to 100 proteins having the highest score and continued with StringDB analysis with 16 proteins. Conclusion: From the GeneCards, Cytoscape, and StringDB data, analysis of protein interactions in cardiac premature senescence showed that the protein-protein interactions with the highest scores were TP53, CDK2, and PTEN.